Petrology And Geochemistry Of The Suhum Basin Granitoid Complex, Ghana: Implications For Crustal Growth During The Rhyacian Orogeny Of The West African Craton. - Kwayisi, D.; Amponsah, P.O.; Awunyo, E.K.; Sapah, M.S.; Sakyi, P.A.; et al. (Journal of African Earth Sciences, 2024)
The Suhum Basin granitoid complex is an important granitoid complex of the Birimian terrane of Ghana for unravelling the crustal growth and evolution of the West African Craton (WAC) during the Rhyacian Eburnean orogeny. Almost the entire Suhum Basin is occupied by an extensive granitoid complex, which contains useful information for constraining debatable plate tectonic issues, especially during the Archean-Paleoproterozoic transition period. We present petrography, whole-rock geochemistry, and mineral chemistry data of biotite, amphibole, and plagioclase to constrain the temperature-pressure conditions of emplacement, petrogenesis, tectonic setting, the evolution of the granitoids complex of the Suhum Basin, and its implications for the crustal growth and evolution of the WAC. Four lithological types; granite gneiss, migmatites, leucogranites, and mafic enclaves, characterise the granitoid complex of the Suhum Basin. Biotites from the granitoid complex have an annite-siderophyllite composition, and that, coupled with their calc-alkaline and I-type signatures, indicates crystallisation of the granitoid complex of the Suhum Basin under oxidised conditions. The medium-to high-K character of the rocks, together with the calc-alkaline nature, may be a reflection of the generation of magma in regions where the mantle wedge might have interacted with enriched fluids from the underlying plate during dehydration. The enrichment of LILE and LREE relative to HREE and HFSE and the negative Eu, Nb-Ta, and Ti anomalies of the granitoids complex may indicate derivation from enriched magma sources with varying degrees of fractionation in an arc environment. Amphibole-plagioclase thermobarometry indicates that the granitoid complex formed at P-T conditions of 600–712 ◦C and 5.2–7.2 kbar, signifying a deeper depth (19–27 km) of emplacement. The overall geochemical data suggest that the rocks formed during a single orogenic event related to a volcanic arc environment where subduction zone components played a role in the generation of their parental magmas. This finding is therefore consistent with the onset of “modern-style” subduction-related pro cesses during the Archean-Paleoproterozoic transitional period.
Research Article
Keywords: Paleoproterozoic; Birimian; Granite Gneiss; Migmatite; West African Craton; Suhum Basin